2003
DOI: 10.1111/j.1365-2621.2003.tb08276.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Polymerase Chain Reaction–Based System for Detecting Salmonella Species from Pork Carcass Sponge Samples

Abstract: Pork carcass sponge samples (n = 230) collected from 10 Taiwanese slaughter plants were screened for Salmonella using 2 methods: BAX® for Screening/Salmonella, a polymerase chain reaction-based detection system and a culture method using SM-ID agar as the selective plating medium. The BAX method identified 14 samples as positive for Salmonella. The 8 samples identified as Salmonella-positive by the SM-ID method were also BAXpositive. Inoculation studies showed BAX detected Salmonella in samples having initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…in BPW was 5.0 x 10 3 CFU / ml. Wu et al (2003) reported that Salmonella spp. was detected by the BAX® system on pork carcass sponge samples with an initial inoculum (prior to enrichment) of 1.4 x 10 1 CFU / ml in the presence of 3.0 x 10 6 CFU / ml of other microbial contaminants.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…in BPW was 5.0 x 10 3 CFU / ml. Wu et al (2003) reported that Salmonella spp. was detected by the BAX® system on pork carcass sponge samples with an initial inoculum (prior to enrichment) of 1.4 x 10 1 CFU / ml in the presence of 3.0 x 10 6 CFU / ml of other microbial contaminants.…”
Section: Analysis Of Resultsmentioning
confidence: 99%